Coordinating ionic and electronic conductivity on 3D porous host enabling deep dense lithium deposition toward high-capacity lithium metal anodes. Issue 37 (13th September 2022) - Yang, Hao; Zheng, Hongfei; Yu, Huaming; Qu, Baihua; Chen, Libao; Niu, Jianmin; Chen, Yuejiao
Abstract : The Li ionic and electronic conductivity on Cu foam is coordinated by the enriched-sparse distributed nano LiF layer, and deep dense Li deposition within the Cu foam skeleton is promoted. Abstract : Engineering composite lithium (Li) metal within three-dimensional (3D) porous skeleton hosts is a feasible strategy to tackle issues of uncontrollable dendrite growth and enormous volume change on Li metal anodes. Nevertheless, the accumulative Li deposition on the top surface of the 3D skeleton remains a harsh challenge that still requires effort. Herein, we develop a rational design involving an enriched-sparse LiF gradient on a Cu foam via facile magnetron sputtering to coordinate ionic and electronic conductivity. The Li ion-conductive LiF gradient guides deep, dense Li deposition within the Cu foam framework, safely preventing surface Li accumulation. As a result, the Cu foam with optimal LiF sputtering time for 40 min (Cu foam/LiF(40)) renders the best synergy of ionic and electronic conduction. Such composite Li anode in the symmetric cell achieves an ultra-long lifespan up to 1700 h at the current density of 2 mA cm −2 with the capacity of 2 mA h cm −2 . This work certifies the decisive significance of coordinating ionic and electronic conductivity for uniform Li deposition on 3D porous hosts and provides a simple and effective avenue to controllably deposit Li in suitable locations for long-term and high-capacity 3D Li metal anodes.